Enhancing the Capacity of Village-Owned Enterprises (BUMDesa) and DAPM Across Ngawi Regency in Responding to the Advancements of the Digitalization Era - Istiana Wijayanti Mala (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of a participatory educational program designed to strengthen the digital capacity of Village Owned Enterprises and the Community Empowerment Trust Fund across Ngawi Regency in responding to the advancement of the digitalization era. The program employed an empirical approach involving thirty eight participants consisting of BUMDesa managers, DAPM administrators, and village officials responsible for rural economic governance. The activities were conducted through interconnected stages comprising socialization, training, mentoring, and evaluation focusing on digital literacy, digital financial administration, and digital marketing adaptation. Empirical findings revealed significant improvement in participants’ conceptual understanding, practical competencies, and adaptive perspectives toward technology based governance. Participants demonstrated stronger capabilities in utilizing digital administrative systems, preparing digital financial records, and developing promotional strategies through social media and marketplace platforms. The participatory learning approach also strengthened collaborative interaction, institutional networking, and organizational responsiveness toward governance innovation. The study concludes that sustainable digital transformation in rural economic institutions requires the integration of technical competence, participatory empowerment, collaborative governance, and continuous institutional adaptation to strengthen accountability, competitiveness, and long term rural economic resilience.